2016
DOI: 10.1177/1043454216659448
|View full text |Cite
|
Sign up to set email alerts
|

Dinutuximab

Abstract: Therapy combining dinutuximab with granulocyte macrophage colony stimulating factor, interleukin 2, and isotretinoin has significant side effects; however, these complications are generally predictable and can be managed proactively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…The unclear pathogenesis of neuroblastoma impedes the development of therapeutic drugs discovery and effective tumor therapy. With decades of efforts, only Unituxin (dinutuximab) was approved by the US Food and Drug Administration as a novel targeted drug in 2015, which can prolong the survival of patients with high-risk NB [ 6 ]. Therefore, clear clarification of mechanisms underlying NB progression is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The unclear pathogenesis of neuroblastoma impedes the development of therapeutic drugs discovery and effective tumor therapy. With decades of efforts, only Unituxin (dinutuximab) was approved by the US Food and Drug Administration as a novel targeted drug in 2015, which can prolong the survival of patients with high-risk NB [ 6 ]. Therefore, clear clarification of mechanisms underlying NB progression is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended gabapentin regimen varies for different anti-GD2 mAbs. For dinutuximab and dinutuximab beta, gabapentin administration starts 2 to 3 days before the infusion or on the day of infusion, 6,21,26 whereas for naxitamab infusions, gabapentin is initiated 5 days before the first infusion. 7 Gabapentin has also been used in combination with tricyclic antidepressants as premedication for anti-GD2 infusions; based on the authors' experience of using tricyclic antidepressants to treat neuropathic pain, desired effects are achieved after at least 2 days of continuous therapy.…”
Section: Gabapentin and Tricyclic Antidepressantsmentioning
confidence: 99%
“…Especially, IL-2 can cause serious adverse reactions such as fever, capillary leak syndrome, and infections. 33 Clinical studies showed that most of the adverse reactions are also seen in regimen containing only retinoic acid with low possibility. 17…”
Section: Dinutuximabmentioning
confidence: 99%